Construction, operation and performance of a chamber for tests of accelerated carbonation - Linares, Douglas; Sánchez, Miguel (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Carbonation phenomenon produces first neutralization of the cement paste and later reinforcement corrosion in concrete structures. Its reaction mechanism is controlled by diffusional steps, which yield a rate which requires several years to obtain an important extension of the neutralization reaction. The present work describes the construction, operation setting and performance of an equipment that accelerates this reaction rate artificially by mean of increasing the carbon dioxide concentration into a controlled atmosphere. This is the first time that such equipment to control humidity and carbon dioxide concentration (main variables that affect the carbonation phenomena) is fabricated and used in Venezuela.